OC-052 Comparative evaluation of outcomes in adolescents with IBD on transfer from paediatric to adult health care services: a case for structured transition. (28th May 2012) - Cole, R; Ashok, D; Kumar, P; Razack, A; Azaz, A; Sebastian, S
Abstract : Introduction: Transition and transfer of adolescent IBD patients to adult health care services is considered suboptimal in surveys. There is limited data on patients undergoing transition and transfer. We aimed to evaluate the impact of transition service on clinical and developmental outcomes of adolescent IBD patients on transfer to adult health care services. Methods: We reviewed records of IBD patients diagnosed in paediatric care who has been transferred to the adult IBD service. We extracted data on their transition and transfer arrangements, disease outcomes, surgery requirements, radiation exposure, medication compliance, alcohol and drug use and growth and development. The data was compared between those who attended transition service with those who did not pass through the transition service. Results: 51 patients were identified (29M and 22F). 38 patients had Crohn`s disease, 11 ulcerative colitis and two indeterminate. The median age at diagnosis was 14 years (range 9–16 years) and the median age at first visit to adult health care was 18 years.35 patients went through the transition system (group A) but 16 had no formalised transition arrangement before transfer (group B). Group A patients had a median of three appointments (range 2–7) in transition clinic before transfer. Significantly higher number of group B patients needed surgery within 2 years of transfer when compared to patients in group A (26% vs 17.1%, p=0.05). Similarly 75% of patients in group B needed at least one admission when compared to only 28.6% of group A patients (p=0.002). Non-attendance to clinics was a higher problem in group A patients with 93.75% having at least one non attendance while 37.1% of group B failed to attend at least one appointment. In addition, drug compliance rates were higher in the transition group when compared to group B (76% and 37.5% respectively p=0.001. Higher proportion of transitioned patients achieved their estimated maximum growth potential when completing adolescence. 31 of the 35 patients in group A proceeded to higher education/and or employment while this was achieved only by 50% of the group B patients. The mean cumulated IBD related radiation exposure was higher was in group B patients (17.04 mSv) when compared to group A (7.48 mSv) (p=0.0001). There was a trend towards higher dependence on opiates and smoking in group B patients. Conclusion: In adolescent IBD patients, transition care is associated with better disease specific and developmental outcomes. Prospective studies of different models of transition care in IBD are needed. Competing interests: None declared.